Psychometric Development of a New Body Image Scale for Breast Cancer Survivors - Biederman, Erika (Health Care Women Int, 2019)
The purpose of this study was to psychometrically test a body image scale for breast cancer survivors (BCS). Data (n=1127 BCSs) were obtained via telephone and mailed questionnaires. Psychometric testing was conducted using Cronbach’s alpha, item-total correlations, factor analysis, linear regression, and Pearson's correlations. Data demonstrated a unidimensional seven-item scale with Cronbach's alpha=0.88 and item-total correlations ranging from 0.367 to 0.829. Construct validity was demonstrated with 45% of the body image variance explained by constructs in the conceptual model [F(14,784) = 48.35, p<0.000]. The body image scale demonstrated high internal consistency reliability, unidimensionality, and construct validity.